2013
DOI: 10.1039/c3cc38486a
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescent organosilane-functionalized carbon dots as temperature probes

Abstract: Organosilane-functionalized carbon dots (SiC-dots) were prepared by a simple one-pot hydrothermal approach. The photoluminescence (PL) properties of the SiC-dots revealed a reversible response toward the temperature (293-343 K). Through Si-O-Si bonding, temperature-sensitive PL SiC-dot films could be easily fabricated on glass substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(99 citation statements)
references
References 40 publications
4
95
0
Order By: Relevance
“…The enhanced non-radiative recombination is possibly the main factor for the PL thermal quenching due to the activation of non-radiative recombination centers with temperature increasing. [33][34][35][36] The PL peak of starch/g-CD phosphors shows a red shift of ∼100 eV from 90 to 370 K, which is generally attributed to stronger electron-phonon interaction as the temperature increases (Fig. 4b).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The enhanced non-radiative recombination is possibly the main factor for the PL thermal quenching due to the activation of non-radiative recombination centers with temperature increasing. [33][34][35][36] The PL peak of starch/g-CD phosphors shows a red shift of ∼100 eV from 90 to 370 K, which is generally attributed to stronger electron-phonon interaction as the temperature increases (Fig. 4b).…”
Section: Resultsmentioning
confidence: 97%
“…The temperature-dependent PL not only provides unique insight into the understanding of the PL mechanisms of QDs, 33 but also offers the potential for the application in temperature sensors. 34 The temperature-dependent PL spectra of the starch/g-CD phosphors (mass ratio: 70 : 1) from 90 to 370 K were recorded as shown in Fig. 4a.…”
Section: Resultsmentioning
confidence: 99%
“…For the characterization of Cdots, XPS has generally been used for the assessment of the elemental composition and the chemical bonds of C-dots in combination with IR. Doping of C-dots with nonmetallic heteroatoms such as N [43,49,56,99,114,121,122,134], S [14,24,46,49,87], Si [50,127,140,141], P [39,49,93], and B [114,142] has been characterized by XPS. A typical example of XPS analysis employed to estimate the surface states and chemical composition of nitrogen and sulfur-codoped C-dots (SNCNs) was displayed in Figure 6 [46].…”
Section: X-ray Photoelectronmentioning
confidence: 99%
“…In the case of IR analysis of C-dots samples, apart from the evaluation of hydroxyl (-OH) and carbonyl (C=O) functional groups on the C-dots surface [41,49,69,127], IR is also able to examine the doping of heteroatoms into the C-dots framework. Important examples include the identification of the presence of amide/amine (-CN/NH 2 ) [15,20,21,[37][38][39][40][41][42][43][44][45][46], alkyl sulfide (C-S) [33,[46][47][48][49], organosiloxane (Si-OSi/Si-O-C) [89,127,140,141], phosphates (P=O and P-O-R) [38,49,93], and boronic acid (B-O and B-N) [114,142,143] moieties attached on the surface of C-dots, providing evidence for introduction of nitrogen (N), sulfur (S), silicon (Si), phosphorus (P), and boron (B) heteroatoms into Cdots. The merits of this technique for the characterization of surface functionalization of C-dots are being low cost, simple, rapid, and easy for sample preparation.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…Chen et al [25] reported a detection method using organosilane-functionalized CDs as temperature probes at 293-343 K. SiC-dot solutions and films both exhibited rapid temperature-dependent PL responses. The temperature induced PL quenching mechanism is related to the temperature enhanced population of nonradiative channels of surface (trap/defect) states [101].…”
Section: Other Detectionsmentioning
confidence: 99%